Management of multiple facial leiomyomas with excision and cervicofacial flap reconstruction in a severe Hemophilia A patient: A case presentation: Cervicofacial flap in Hemophilia A - Hack, Sholem; Lubetsky, Aaron; Tessler, Idit; Remer, Eric (Journal of Surgery and Medicine, 2026)
Cutaneous leiomyomas are rare, benign, smooth-muscle tumors that are particularly uncommon on the face. Surgical management of cutaneous leiomyomas in patients with severe Hemophilia A is challenging because of the substantial risk of bleeding, particularly when regional flap reconstruction is required. Here, we report the case of a 64-year-old male with severe Hemophilia A who presented with multiple painful cutaneous nodules in the right preauricular and submandibular region. MRI and biopsy confirmed multiple cutaneous leiomyomas of piloleiomyoma and angioleiomyoma types. A multidisciplinary team developed a perioperative recombinant factor VIII protocol to minimize bleeding risk. Surgical excision with a narrow 5 mm margin was performed, followed by cervicofacial flap reconstruction. The patient’s intra- and immediate postoperative course was uneventful. Flap viability was maintained despite minor marginal ischemia, which resolved with conservative management. Factor VIII levels remained within therapeutic range throughout hospitalization, and histopathology confirmed the leiomyomas’ benign status. Renal cancer screening was recommended because of the association with multiple leiomyomas. The patient achieved satisfactory aesthetic and functional recovery without bleeding complications. This case highlights that complex facial excision and flap reconstruction can be performed safely in patients with severe Hemophilia A using a tailored factor VIII replacement protocol and underscores the importance of multidisciplinary perioperative planning in such cases.